Declining Levels and Bioavailability of IGF-I in Cardiovascular Aging Associate With QT Prolongation–Results From the 1946 British Birth Cohort - Charalambous, Christos; Moon, James C.; Holly, Jeff M. P.; Chaturvedi, Nishi; Hughes, Alun D.; Captur, Gabriella (Frontiers in Cardiovascular Medicine, 2022)
Background: As people age, circulating levels of insulin-like growth factors (IGFs) and IGF binding protein 3 (IGFBP-3) decline. In rat cardiomyocytes, IGF-I has been shown to regulate sarcolemmal potassium and late sodium channel activity thus impacting cardiac repolarization and the heart rate-corrected QT (QTc). However, the relationship between IGFs and IGFBP-3 with the QTc interval in humans, is unknown. Objectives: To examine associations of IGFs and IGFBP-3 with QTc interval in an older age population-based cohort. Methods: Participants were from the 1946 Medical Research Council National Survey of Health and Development British birth cohort. Biomarkers from blood samples at age 53 and 60-64 years (y, exposures) included IGF-I/II, IGFBP-3, IGF-I/IGFBP-3 ratio and the change (Δ) in marker levels between 60-64y and 53y. QTc (outcome) was recorded from electrocardiograms at the 60–64y timepoint. Generalized linear multivariable models with adjustments for relevant demographic and clinical factors, were used for complete-cases and repeated after multiple imputation. Results: 1448 participants were included (48.3% men; QTc mean 414ms interquartile range 26ms). Univariate analysis revealed an association between low IGF-I and IGF-I/IGFBP-3 ratio at 60-64y with QTc prolongation (respectively: β -0.30ms/nmol/L, [95% confidence intervals -0.44, -0.17], p<0.001; β 28.9ms/unit [-41.93, -15.50], p<0.001). No association with QTc was found for IGF biomarkers sampled at 53y, however both ΔIGF-I and ΔIGF-I/IGFBP-3 ratio were negatively associated with QTc (β 0.04ms/nmol/L [-0.08, -0.008], p=0.019; β -2.44ms/unit [ 4.17, -0.67], p=0.007). In fully adjusted imputed models, low IGF-I and IGF-I/IGFBP-3 ratio at 60-64y (β -0.21ms/nmol/L [-0.39, -0.04], p=0.017; β -20.14ms/unit [-36.28, -3.99], p=0.015), steeper decline in ΔIGF-I (β -0.05ms/nmol/L/10y [-0.10, -0.002], p=0.042) and shallower rise in ΔIGF-I/IGFBP-3 ratio over a decade (β 2.16ms/unit/10y [-4.23, -0.09], p=0.041), were all independently associated with QTc prolongation. Independent associations with QTc were also confirmed for other known covariates: female sex, left ventricular mass and blood potassium levels. Conclusion: Over a decade, in an old population-based cohort, declining levels and bioavailability of IGF-I associate with prolongation of QTc interval. As QTc prolongation associates with increased risk for sudden death even in apparently healthy people, further research into the antiarrhythmic effects of IGF-I on cardiomyocytes is warranted.